Building a financial conditions index for the euro area and selected euro area countries: what does it tell us about the crisis? - Eleni Angelopoulou; Hiona Balfoussia; Heather Gibson (European Central Bank (ECB), 2013)
In this paper we construct Financial Conditions Indices (FCIs) for the euro area, for the period 2003 to 2011, using a wide range of prices, quantities, spreads and survey data, grounded in the theoretical literature. One FCI includes monetary policy variables, while two versions without monetary policy are also constructed, enabling us to study the impact of monetary policy on financial conditions. The FCIs constructed fit in well with a narrative of financial conditions since the creation of the monetary union. FCIs for individual euro area countries are also provided, with a view to comparing financial conditions in core and periphery countries. There is evidence of significant divergence both before and during the crisis, which becomes less pronounced when monetary policy variables are included in the FCI. However, the impact of monetary policy on financial conditions appears not to be entirely symmetric across the euro area.
Keywords: E52; E51; E61; E63; E65; 330; financial conditions; financial crisis; monetary policy